Developing Multiple Intelligences through Different Learning Styles: An Integrated Approach to Learner-centered Pedagogy - Mohammad Danish Mahmood; Bareq Raad Raheem; Raashid Nehal (Newinera Publisher, 2022)
The present paper deals with the theoretical underpinnings of various learning styles by Carl Jung and the different types of intelligences by Howard Gardner. The purpose of this paper is to integrate various learning styles with different types of intelligences. The main concern here is to understand how each learning style could be incorporated with every intelligence so as to make the pedagogy a learner-centered approach.